The possibility of 3D-origmi system as a tourism promotion tool for Japan - RISA OGAWA; TAKAYUKI FUJIMOTO (Journal of Advanced Research in Social Sciences and Humanities, 2018)
Aim: As part of this research, we created a mobile app that illustrates the steps involved in folding an origami paper, thereby introducing people to a facet of Japanese traditional culture. Numerous marketing resources are needed to spread the word about Japanese. The authors believe that traditional Japanese lifestyle culture is beautiful for many reasons.Method: Origami was studied as a tool for tourism through a qualitative method.Findings: Origami describes a set of meanings that are psychologically significant in representing forms and the functional study of line drawings, as demonstrated by the results. Some preliminary data suggest that the number of international visitors to Japan is rising due to ongoing promotion efforts.Implications/Novel contribution: Since few studies have been done on 3-D Origami’s potential for boosting tourism, the current study stands out as original.